PERT’s Recommendations Included in New Report on the Economic Development of Offi cial Language Minority Communities - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Supporting the Economic Development of Québec’s English-Speaking Communities - Provincial Employment Roundtable (PERT) (2023)
The Provincial Employment Roundtable (PERT) is pleased to submit this brief and present it to the Standing Committee on Official Languages to contribute to its study of the economic development of official language minority communities (OLMCs). We believe this is an important study, which we hope will shed light on the needs of our community and lead to the development of new government actions that address the economic development challenges in Québec’s English-speaking communities, particularly in employment and employability.
Keywords: Official Language Minority Community (OLMC)

Press Release: New study reveals economic precarity and limit job supports for racialized communities and English-speaking immigrants in Québec. - Provincial Employment Roundtable (PERT) (2023)

Une nouvelle étude révèle la précarité économique et l’insuffisance des aides à l’emploi pour les communautés racialisées et les immigrants d’expression anglaise au Québec - Provincial Employment Roundtable (PERT) (2023)

Economic Development and Community Vitality : A Report on Federal Funding Streams Available to the English-speaking Community of Quebec - Quebec Community Groups Network (QCGN); Community Economic Development and Employability Corporation (CEDEC); Youth Employment Services (YES) (2023)
The following report provides an overview of the main federal funding streams for the English-speaking community in Quebec (ESCQ) along with the French-speaking community in the rest of Canada. This includes an overview and analysis of the Canada Economic Development for Quebec Regions (CED-Q), including the Official Languages Economic Development Initiative (EDI) and other official language minority communities (OLMCs) specific funding streams: Regional Economic Growth through Innovation (REGI), the Quebec Economic Development Program (QEDP), and the Community Futures Program (CFP). As a means of comparing funding levels for the French-speaking community outside of Quebec, this study also reviews Canada Economic Development for the Rest of Canada (CED-ROC).
Keywords: Official Language Minority Community (OLMC)

Stanstead Dinner and Show series kicks off collaborative effort to increase local tourism - Community Economic Development and Employability Corporation (CEDEC) (2023)

Une série de dîners-spectacles donne le coup d’envoi à un effort collaboratif pour augmenter le tourisme local - Community Economic Development and Employability Corporation (CEDEC) (2023)

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)

CEDEC hopeful Official Languages Act Action Plan will have long-term impact and meaningful difference to ESCQ vitality - Community Economic Development and Employability Corporation (CEDEC) (2023)

La CEDEC a bon espoir que le plan d'action pour les langues officielles aura un effet à long terme et fera une importante différence sur la vitalité de la communauté d'expression anglaise du Québec - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)

Le magazine en ligne de la CEDEC : De meilleures économies pour de meilleures vies - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)

Le magazine en ligne de la CEDEC : De meilleures économies pour de meilleures vies - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2023)

Residential Precarity : Youth and Housing in Québec’s Urban Centres - Rodriguez, Chloe (Y4Y Québec, 2023)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)

Working Together for a More Vital Community : The 2022-2027 Community Developmet Plan for English-speaking Quebec - Community Vitality Roundtables (Quebec Community Groups Network (QCGN), 2022)
The community sector serving English-speaking Quebec cultivates a sustained, ongoing capacity to collect, analyze, and share information (qualitative and quantitative) necessary to more deeply understand our community.

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Council for Magdalen Islanders (CAMI), 2022)
In recent years, the English-speaking community of the Magdalen Islands has been engaged in a structured approach to community development. This has been guided by knowledge development and mobilization, strategic planning, and partnerships with local stakeholders to develop and implement relevant projects that meet the needs of the community.
Keywords: Official Language Minority Community (OLMC)

Life without Compromise : Youth Forum 2021 - Kayla; Fequet, Latesha (2021)

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Richardson, Mary; Zettl, Mary; Harrison, Kim (Community Health and Social Services Network (CHSSN), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people filled out the survey and nine FGD were held in a total of six communities (with a total of 82 youth).

Social Portrait of the Greenfield Park Borough (Ville de Longueuil) - Corporation de développement communautaire de l’agglomération de Longueuil (2020)

Impact Report 2019-2020 - 4Korners (2020)

Rapport d'impact 2019-2020 - 4Korners (2020)

Annual General Meeting : Coastal Summit Series 2020 - Coasters Association (2020)

Coastal Summit Report 2020 - Fequet, Shelley (2020)
A virtual Coastal summit was organized and carried out by the Coasters Association in the fall of 2020. A total of 156 individuals participated in a series of Zoom sessions which had two objectives. First, sharing information about the social and economic initiatives of the Coasters Association; and second, how to support the economic and social development of the Lower North Shore.
Keywords: Official Language Minority Community (OLMC)

Rapport sommet côtier 2020 - Fequet, Shelley (2020)
Un sommet du littoral virtuel a été organisé et réalisé par la Coasters Association à l’automne 2020. Au total, ce sont 156 personnes qui ont participé à une série de réunions Zoom qui visaient deux objectifs : tout d’abord, partager d l’information sur les initiatives sociales et économiques de la Coasters Association ; puis, déterminer la façon de soutenir le développement économique et social de la Basse-Côte-Nord.
Keywords: Official Language Minority Community (OLMC)

Brief to Appele Quebec on Bill 40 : an Act to Amend Mainly the Education Act with Regard to School Organization and Governance - Buck, John (Community Economic Development and Employability Corporation (CEDEC), 2019)
The Community Economic Development and Employability Corporation, CEDEC, has been intimately involved over the last twenty-five years in developing and enhancing the vitality of the English-speaking Minority Community of Quebec. CEDEC is committed to improving the economic well-being of communities. It is a hub of innovative research and practice focused on enhancing economic activity that benefits communities through public, private, and civil society collaboration.

Guide à l'intention du récolteur : Pour le démarrage d'une entreprise de réolte de matières premières naturelles sur la Basse-Côte-Nord (QC) - Poole, Jessica (2019)

Harvester's Guide : Starting a Raw Materials Harvesting Business : Lower North Shore, QC - Poole, Jessica (2019)

Strategic Priorities Forum : 2018 – 2019 Priorities of the English-speaking Community of Quebec and Annual Report of the Priority Setting Steering Committee - Quebec Community Groups Network (QCGN) (2019)

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of the Magdalen Islands - Richardson, Mary; Maynard, Hugh; Burke, Helena; Brinklow, Laurie; Mulligan, Marleen (Council for Magdalen Islanders (CAMI), 2019)
In recent years, the English-speaking community of the Magdalen Islands has been engaged in a structured approach to community development. This has been guided by knowledge development and mobilization, strategic planning, and partnerships with local stakeholders to develop and implement relevant projects that meet the needs of the community.
Keywords: Official Language Minority Community (OLMC)

NDG Community Strategic Action Plan 2016-2021 : List of Annexe : Part II - NDG Community Council (NDGCC) (2018)
This document is the first of three that collectively represent the NDG Community Strate- gic Plan 2016-2021. Part I is a report on the strategic planning and action planning pro- cess and presents the context, tools and outcomes of the NDG Community Strategic Plan. Part II includes annexes to this report with details, tools and other data. Part III presents the Action Plan 2018-2021.

NDG Community Strategic Action Plan 2016-2021 : Part I - NDG Community Council (NDGCC) (2018)
This document is the first of three that collectively represent the NDG Community Strate- gic Plan 2016-2021. Part I is a report on the strategic planning and action planning pro- cess and presents the context, tools and outcomes of the NDG Community Strategic Plan. Part II includes annexes to this report with details, tools and other data. Part III presents the Action Plan 2018-2021.

NDG Community Strategic Action Plan 2016-2021 : Part III - NDG Community Council (NDGCC) (2018)
This document is the first of three that collectively represent the NDG Community Strate- gic Plan 2016-2021. Part I is a report on the strategic planning and action planning pro- cess and presents the context, tools and outcomes of the NDG Community Strategic Plan. Part II includes annexes to this report with details, tools and other data. Part III presents the Action Plan 2018-2021.

Regional Tourism Action Plan for the English-speaking Community of the Gaspé and Magdalen Islands 2018-2023 - Harrison, Kim (Committee for Anglophone Social Action (CASA), 2018)
The Committee for Anglophone Social Action (CASA) works to build and strengthen the vitality of the English-speaking community of the Gaspé Coast This regional tourism action plan has been developed to foster the increased participation in the tourism industry by English speakers and encourage a greater number of English speakers to visit the Gaspé Coast and the Magdalen Islands. The English-speaking community of the region faces many socio-economic challenges as compared to the francophone population. Increased participation in tourism industry would generate social and economic benefits at the individual, organizational and community level. A recent study commissioned by the Community Economic Development and Employability Committee has indicated a high level of interest by American and Ontarian travellers in visiting the attractions of the English-speaking Quebec, as well as the desire to receive English services when visiting the province.
Keywords: Official Language Minority Community (OLMC)

Grant Writing Principles - Park, June (2018)

Final Report: Emploi Quebec: Coasters Association - Gallibois-Robertson, Melanie (Coasters Association, 2017)

Action Plan : Westhaven Neighborhood Committee - Westhaven Neighborhood Committee (2017)

Tourism 2025 : CEDEC's Plan for Creating 46,900 Jobs and Adding $5.2 Billion to the Economy - Community Economic Development and Employability Corporation (CEDEC) (2017)

Tourisme 2025 : Le plan de la CEDEC pour cré2r 46 9000 emplois et ajouter 5.2 milliards de dollar à l'économie - Community Economic Development and Employability Corporation (CEDEC) (2017)

NDG : A snapshot : Quality of life conference / NDG : Un aperçu : 2017 conférence sur la qualité de vie - NDG Community Council (NDGCC) (2017)

Cultural Tourism and Touring Research : Funded by Innovation, Science and Economic Development Canada - Nasrallah, Dimitri; English-Language Arts Network (ELAN) (English-Language Arts Network (ELAN), 2016)
ELAN Quebec’s core objectives over the next four years are to cultivate and expand upon communication, research, and market-access networks that the organization has already initiated in the English-speaking communities of Quebec (ESCQ). ELAN will execute its network-development strategy through the pursuit of numerous concurrent activities that involve existing and future partnerships with different stakeholders. Activities have been devised across two broad phases: Phase 1 focuses on cultivating and strengthening various networks within Quebec. Phase 2 focuses on expanding the various networks cultivated in Phase 1 beyond Quebec’s borders, to find new audiences for ESCQ culture in Ontario, the Maritimes, and the northeastern United States.
Keywords: Official Language Minority Community (OLMC)

Children 0 to 5 and their Parents : RTS de la Gaspésie / Enfants de 0 à 5 ans et leurs Parents : RTS de la Gaspésie - Community Health and Social Services Network (CHSSN) (2016)

Literature Review - Mulligan, Marleen (Council for Magdalen Islanders (CAMI), 2016)
Small, rural and remote regions around the world are transforming due to forces outside of their control such as globalization, neoliberalism and climate change. While often characterized as being in a state of decline due to dwindling populations and employment opportunities, this literature review reveals that numerous small communities are finding ways to capitalize on these forces of change. The review focuses on regions similar to the Magdalen Islands – situated in the western world, shaped by colonial powers, and relatively well off. The common pattern found among the successful cases is a development approach that is internally focused, builds on existing assets (human, physical and intangible) and is scale appropriate with results that are, therefore necessarily unique to each community. These cases all include senior government support, especially in the form of funding, and in some instances, capacity building, that allows community members to carry the torch and take up the work of revitalizing their community in the ways they deem appropriate.

A Guide to your Visit on the Lower North Shore - Robertson, Melanie (2016)

NDG Community Action Plan 2015 - NDG Community Council (NDGCC) (2015)

Youth Development Initiatives - Coasters Association (2015)
The Coasters Association has had many achievements over the years regarding youth initiatives, and priority areas have been identified. These achievements have contributed to the development and vitality of the region’s communities; however, there are many challenges that remain to hinder the future development and sustainability of the region.

NDG Community Action Plan 2014 - NDG Community Council (NDGCC) (2014)

NDG Community Strategic Plan 2013-2016 - NDG Community Council (NDGCC) (2014)

Le Canada, le bilinguisme et le commerce - Arcand, Alan; Le Conference Board du Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
Le français est l’une des principales langues mondiales. Selon l’Organisation internationale de la francophonie (OIF), au moins 220 millions de personnes le parlent dans le monde1. C’est la langue officielle de tous les organismes des Nations unies et d’un grand nombre d’organisations internationales. Le français a pris naissance en France et s’est répandu grâce à l’expansion de ce pays outre-mer. Actuellement, quelque 30 pays dans le monde, dont le Canada, comptent le français parmi leurs langues officielles.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Economic Development Finding Aid - Eastern Townships Resource Centre (ETRC) (2013)

L'économie créative et les communautés anglophones au Québec: Rapport préparé pour Industrie Canada par Tracy Zhang - Zhang, Tracy (Quebec English-speaking Communities Research Network (QUESCREN), 2012)
L’économie créative et les communautés anglophones au Québec présente les résultats préliminaires d’une étude comprenant un groupe de discussion, des entrevues privées avec des intervenants clés et des recherches documentaires. Le rapport démontre que l’idée d’économie créative est utile au suivi du développement culturel et économique des communautés anglophones du Québec (CAQ). Les anglophones québécois constituent la plus importante communauté minoritaire de langue officielle provinciale au Canada. Au cours des dernières décennies, la composition de cette population est devenue de plus en plus complexe et multiculturelle. Parallèlement à ces changements démographiques, l’influence de la culture anglophone québécoise a aussi évolué. On dit qu’une proportion particulièrement élevée d’anglophones est engagée dans le secteur des arts, de la culture et du patrimoine. Dans ce contexte, les organismes du secteur jouent un rôle croissant dans le développement socioéconomique des CAQ. Le présent rapport révèle les préoccupations grandissantes des représentants de certains organismes de ce type qui ont participé à l’étude en ce qui a trait à la manière d’appliquer la théorie de l’économie créative de façon à créer des modèles de développement culturel et économique efficaces pour les CAQ.
Keywords: Official Language Minority Community (OLMC)

The Creative Economy and the English Speaking Communities in Quebec : Report Submitted to Industry Canada by Tracy Zhang on Behalf of the Quebec English-speaking Communities Research Network (QUESCREN) - Zhang, Tracy (Quebec English-speaking Communities Research Network (QUESCREN), 2012)
The Creative Economy and English-Speaking Communities in Quebec presents preliminary research results based on a focus group, private key informant interviews, and bibliographical research. It demonstrates that the concepts of the creative economy are useful in charting cultural and economic development for the English-speaking communities in Quebec (ESCQ). The English-speaking population in Quebec forms the largest provincial Official Language Minority Community in Canada. In recent decades, the composition of this population has become increasingly complex and multicultural. Parallel to this demographic shift, the influence of English-language Quebec culture has also evolved. English-speakers are said to have a high participation rate in the arts, culture and heritage sectors. In this context, organizations from these sectors are increasingly involved in supporting the socioeconomic development of the ESCQ. This report reflects growing concerns on the part of representatives of some of these organizations who participated in the study over how to apply the creative economy theory to generate effective models of cultural-economic development for the ESCQ.
Keywords: Official Language Minority Community (OLMC)

Business Vitality Initiative : Community Handbook - Community Economic Development and Employability Corporation (CEDEC) (2010)
If you’re not asking these questions, it’s unlikely you’re maximizing the potential of your community. Communities identifying their strengths, their gaps and their unexplored opportunities— that is what’s behind the BVI, a measurement and action process that helps communities harness their business potential. It has been designed to help communities assess their capacity to work with and support entrepreneurs, and to foster business growth. The BVI has been employed in communities across Canada (and recently in Australia) by a team based in Nelson, BC. The CIEL/BVI Team has been nominated for BC’s top award in community economic development and most recently won an award as the region’s most innovative organization. The BVI measures the perceptions of community leaders, business people and citizens about the current business environment in the community and compares the scores to those from other communities using a unique graphical index (the Business Vitality Index).

Business Vitality Initiative : Facilitator Handbook - Community Economic Development and Employability Corporation (CEDEC) (2010)
The Purpose of this Manual: The BVI includes two highly structured public meetings which require expert facilitation. This manual is a basic resource for facilitators. Other necessary resources include: • The BVI PowerPoint presentation • The BVI Community Handbook • Discussions with CIEL management • Discussions with the Community Sponsor • A BVI Assessment Report and Final Report from another community

Business vitality initiative : Manuel de l'animateur - Community Economic Development and Employability Corporation (CEDEC) (2010)
Le Business Vitality Initiative (BVI) comprend deux assemblées publiques très structurées qui doivent être animées par un expert. Le Manuel est la ressource principale des animateurs de ces assemblées, mais d’autres ressources sont aussi mises à leur disposition, notamment : • le diaporama sur le BVI; • le Manuel de la communauté – BVI; • le compte rendu des discussions avec la direction du CIEL; • le compte rendu des discussions avec l’organisme de parrainage communautaire; • un rapport d’évaluation dans le cadre du BVI et le rapport définitif d’une autre communauté.

Appendicies for Cultural Tourism and Touring Research - Nasrallah, Dimitri (English-Language Arts Network (ELAN), 2009)

Pas de talents à perdre : priorité à l’alphabétisation - Charest, Jean; David, Françoise; Dumont, Mario; Khadir, Amir; Marois, Pauline; Rainville, Guy; La Coalition pour l’alphabétisation (2008)

A Policy Framework for Economic Development and Employability for the English-speaking Communities of Quebec : Submitted to the Quebec Community Groups Network (QCGN) - Qu'anglo (2008)
Through previous research and following a number of community consultations, the QCGN had determined that there is a need for initiatives that will enable the English-speaking Communities of Quebec to work more effectively with the Government of Canada, the Government of Quebec, school boards and relevant stakeholders to more fully participate in the economy of province. Given the continuing exodus of educated and trained anglophones to seek employment opportunities elsewhere, and the difficulties faced by particular segments of the population, especially youth, visible minorities and newly arrived immigrants, who choose to seek employment and self-employment within Quebec, it was determined that an integrated and targeted approach to improve the economic development prospects of the community was required.
Keywords: Official Language Minority Community (OLMC)

The Development of an Action Plan to Expand Volunteerism & Leadership on the Lower North Shore of Quebec - Buckle, Heidi (Coasters Association, 2005)
Throughout phase one of this project, a needs assessment study was successfully carried out to identify the needs of the one hundred and thirteen (113) community organizations and twenty-one (21) regional organizations on the coast; along with a volunteer awareness campaign and the building of a strong volunteer base for the fifteen (15) communities of the Lower North Shore of Quebec. This study was then distributed to all the organizations, the working group, the Board of Directors of the Coasters Association and the volunteers who participated in this project. It has been shared with various Quebec Community Group Networks and HRD Community Table groups across the province, along with various federal and provincial government departments. It has been used as a working tool by many organizations on and off the coast.

Strategic Development Plan Oriented Towards Tourism : Phase I (2006-2008) - Gagnon, Luc (2005)
Entry Island constitutes an undeniable attraction for visitors to the Magdalen Islands, as well as for Madelinots. About 9,000 people visit the island to holiday or on excursions each year. However, the lack of appropriate facilities and services makes it difficult to receive visitors properly. Failings in this area lead to degradation of the environment and reduced quality of life for residents. Recognizing the need to receive its guests in an appropriate manner and to better direct their visit - as well as recognizing the opportunity to offer them an exclusive, quality product - the Entry Island Harbour Authority hired Luc Gagnon, an anthropology student at Universite Laval to accompany the community through a process of strategic development planning oriented towards tourism. This plan concerns Entry Island exclusively, and is meant to complement the tourism development plan adopted by Tourisme lies de la Madeleine.

Remote Site Information Technology Assessment for the Municipality of Bonne-Esperance Lower North Shore, Quebec - Coasters Association (2004)
Information technologies (computers, Internet, etc.) are an essential component of modern economic development strategies. The Lower North Shore has lagged behind other areas in terms of equipment, infrastructure and human resource capacity for using information technologies as an integral part of their community development efforts (i.e. no hi-speed access.) Recent innovations in this area allow for the reception of hi-speed (broadband) Internet reception via satellite; with establishment of local area networks (LANs) connected to each satellite point-of-delivery, the prospect exists for significant improvements to the information technology capacity of remote locations such as MBE, as well as local revenue generation from service provision once the LAN is established.